2012
DOI: 10.1172/jci65459
|View full text |Cite
|
Sign up to set email alerts
|

Th9 cells promote antitumor immune responses in vivo

Abstract: Th9 cells are a subset of CD4 + Th cells that produce the pleiotropic cytokine IL-9. IL-9/Th9 can function as both positive and negative regulators of immune response, but the role of IL-9/Th9 in tumor immunity is unknown. We examined the role of IL-9/Th9 in a model of pulmonary melanoma in mice. Lack of IL-9 enhanced tumor growth, while tumor-specific Th9 cell treatment promoted stronger antitumor responses in both prophylactic and therapeutic models. Th9 cells also elicited strong host antitumor CD8 + CTL re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
322
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(343 citation statements)
references
References 51 publications
12
322
1
4
Order By: Relevance
“…S7). Taken all together, these results thus far suggested that Tc9 cells may kill tumor cells independent of their secreted IFN-γ, possibly by using the cytolytic enzymes, and IL-9 provided critical help to their migration into tumor sites to exert effector function, which is an effect of IL-9 that has been extensively elucidated in our previous studies (15,17). Discussion CD8 + CTLs are thought to play a crucial role in tumor rejection, and extensive focus has been devoted to the study of CD8 + T cells in adoptive transfer protocols.…”
Section: Tc9 Cells Are Less Exhausted and Developed Into Full Effectomentioning
confidence: 57%
See 2 more Smart Citations
“…S7). Taken all together, these results thus far suggested that Tc9 cells may kill tumor cells independent of their secreted IFN-γ, possibly by using the cytolytic enzymes, and IL-9 provided critical help to their migration into tumor sites to exert effector function, which is an effect of IL-9 that has been extensively elucidated in our previous studies (15,17). Discussion CD8 + CTLs are thought to play a crucial role in tumor rejection, and extensive focus has been devoted to the study of CD8 + T cells in adoptive transfer protocols.…”
Section: Tc9 Cells Are Less Exhausted and Developed Into Full Effectomentioning
confidence: 57%
“…Interestingly, when mice were treated with IL-9-neutralizing antibodies, Tc9 cells largely failed to migrate into tumor tissues to exert long-lasting antitumor therapeutic effect. Given the important role of IL-9 in provoking inflammation in tumor sites and recruitment of lymphocytes (15,17), our results suggested that IL-9 secreted by Tc9 cells played an indispensible role for the homing of these cytolytic Tc1-like cells to tumor tissues and killing of tumor cells. These findings thus indicated that IL-9 rather than IFN-γ might be the critical cytokine contributed to the tumor destruction mediated by Tc9 cells.…”
Section: Tc9 Cells Are Less Exhausted and Developed Into Full Effectomentioning
confidence: 78%
See 1 more Smart Citation
“…Intriguingly, Th9 cells also appear to regulate tumor immunity. Although IL-9 and Th9 cells exerted antitumor activity in some solid tumor models (7,8), IL-9 actually promoted lymphoma development in other models (9). IL-9 is thus an important cytokine with multiple functions in the regulation of immune responses.…”
mentioning
confidence: 99%
“…Purwar et al reported that administration of rIL-9 or Th9 cells to tumor-bearing mice inhibited melanoma growth, through a mechanism dependent of mast cells [43]. In turn, Lu et al described another antitumor effect of IL-9 on melanoma lung metastasis, which through the induction of local CCL20 expression in the tumor microenvironment, led to an enhanced recruitment of dendritic cells and cytotoxic CD8 + T cells at the tumor site [58]. The ability of IL-9 to induce the secretion of chemotactic factors was also largely described in airway inflammatory pathologies [59].…”
mentioning
confidence: 99%